Development of chitosan–poly(acrylic acid) nanoparticles for delivery of 5-fluorouracil - Kakde, Deepak; Parashar, A.; Chadhar, V.; Kakde, R.; Patil, A. T. (Current Research in Pharmaceutical Sciences, 2011)
The present study was aimed at developing and exploring the use of chitosan–poly(acrylic acid) nanoparticles for delivery of anti-cancer drug 5-fluorouracil. Chitosan (CS)–poly(acrylic acid) (PAA) complex nanoparticles, have been prepared by dropping method. The physicochemical properties of nanoparticles were investigated by using,FT-IR,dynamic light scattering, transmission electron microscope and zeta potential. TEM study revealed surface properties of the systems. It was also observed that the prepared nanoparticles carried a positive charge with the size in the range from 100 to 210 nm at pH 4.5. The system was found to have good drug-loading capacity with reduced drug release rate. The encapsulation efficiency of nanoparticle was found to be 78% at pH 4.5. The release rate of drug was pH dependent and found to be more sustaining in pH 4.5 while at pH 7.4, nanoparticles have core shell fuzzy structure. However, the system was suitable for prolonged delivery of an anti-cancer drug by in vitro.